Organização temporal na locução do telejornalista. - Isabel Teixeira Nascimento (2008)
The aim of this research was to study the speech temporal organization of offs in factual news readby newsreaders, more specifically the speech rate, pauses and sound sequences. The corpus iscomprised of 18 offs delivered by eight newsreaders and by eight non-professionals.To analyze the temporal organization the following parameters were studied: speech time,articulation time, speech rate, articulation rate, number and mean duration of pauses, number ofsyllables, mean duration of sound sequences and number of sound sequences. The data wererecorded in a sound proof cabin. They were acoustically analyzed using the software Praat 4.4.07 andstatistically analyzed using the software Microsoft Excel® 2000 and Minitab 15.From the data analysis it was observed that newsreaders present longer speech and articulation timeand shorter speech rate. They also tend to have more sound sequences and less mean duration ofsound sequences. As to the pauses it was verified that the newsreaders showed more pauses withshort mean duration. It was also observed a greater number of pauses placed in the sentences andaverage size pauses as well.The results indicate a segmented newsreading with more pauses and a lower speech rate to betterarticulate the sounds. The aim is to associate the reading to the image and to get the viewersattention and comprehension.